Signifying the signs of virtues, vices, and supernatural in Raksasa Penjaga Gunung Merapi and The Legend Of Sleepy Hollow - Pramugita, Khoirotun Dwi; Silalahi, Pininta Veronika (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2024)
This study aims to investigate the signs of virtues, vices, and supernatural that are contained in folktales Raksasa Penjaga Gunung Merapi and The Legend of Sleepy Hollow. Using Pierce's semiotics technique, the study selected two folktales Raksasa Penjaga Gunung Merapi from Indonesia and The Legend of Sleepy Hollow, from America—to complete it by means of their indications of virtue, vices, and supernatural. In this paper, from these two folktales, the semiotic events of signs of virtues, vices, and supernatural from a qualitative perspective. This paper investigates virtues and vices using Aristotle's theory. Furthermore examines the supernatural applying Jonathan C. Smith's thesis. According to the investigation, qualities were split into nine categories: courage, temperance, generous, humility, patience, truthfulness, clever, friendliness, and modesty. There are seven varieties of vices: fear, insensible, stingy, lack of spirit, understatement, surly, and shyness. At last, the supernatural is split into six: telekinesis, extrasensory perception (telepathy, clairvoyance, and precognition), psychokinesis, mediumship, astrology and fortune telling.